The usefulness of a contrast agent and gradient-recalled acquisition in a steady-state imaging sequence for magnetic resonance imaging-guided noninvasive ultrasound surgery - Schenck, John F.; Hynynen, Kullervo; Unger, Evan; Darkazanli, Ammar; Damianou, Christakis A. (My University, 1994)
Rationale and Objectives. The ability of magnetic resonance imaging to detect small temperature elevations from focused ultrasound surgery beams was studied. In addition, the value of a contrast agent in delineating the necrosed tissue volume was investigated. materials and methods. Gradient-recalled acquisition in a steady state (GRASS) T1-weighted images were used to follow the temperature elevation and tissue changes during 2-minute sonications in the thigh muscles of 10 rabbits. The effects of the treatment on the vascular network was investigated by injecting a contrast agent bolus before or after the son-ication. Results. The signal intensity decreased during the sonica-tion, and the reduction was directly proportional to the applied power and increase in temperature. The signal intensity returned gradually back to baseline after the ultrasound was turned off. Injection of the contrast agent increased the signal intensity in muscle, but not in the necrosed tissue. The dimensions of the delineated tissue volume were the same as mca-sured from the T2-weightcd fast-spin-echo images and postmortem tissue examination. Conclusions. These results indicate that magnetic resonance imaging can be used to detect temperature elevations that do not cause tissue damage and that contrast agent can be used to delineate the necrosed tissue volume. © 1994. J.B. Lippincott Company.
Keywords: Contrast agent; Magnetic resonance imaging; Surgery; Ultrasound